RESILIENCE: Phase III Randomized, Double-Blind Trial Comparing Sorafenib With Capecitabine Versus Placebo With Capecitabine in Locally Advanced or Metastatic HER2-Negative Breast Cancer - Baselga, J.; Zamagni, C.; Gómez, P.; Bermejo, B.; Nagai, S.; Melichar, B.; Chan, Arlene; Mángel, L.; Bergh, J.; Costa, F.; Gómez, H.; Gradishar, W.; et al. (2017)
© 2017. Introduction: Sorafenib is a multikinase inhibitor with antiangiogenic/antiproliferative activity. In this randomized, double-blind, placebo-controlled phase III trial we assessed first- or second-line capecitabine with sorafenib or placebo in patients with locally advanced/metastatic HER2-negative breast cancer resistant to a taxane and anthracycline and with known estrogen/progesterone receptor status. Patients and Methods: A total of 537 patients were randomized to capecitabine 1000 mg/m 2 orally twice per day for days 1 to 14 every 21 days with oral sorafenib 600 mg/d or placebo. The primary end point was progression-free survival (PFS). Patients were stratified according to hormone receptor status, previous chemotherapies for metastatic breast cancer, and geographic region. Results: Treatment with sorafenib with capecitabine, compared with capecitabine with placebo, did not prolong median PFS (5.5 vs. 5.4 months; hazard ratio [HR], 0.973; 95% confidence interval [CI] , 0.779-1.217; P = .811) or overall survival (OS; 18.9 vs. 20.3 months; HR, 1.195; 95% CI, 0.943-1.513; P = .140); or enhance overall response rate (ORR; 13.5% vs. 15.5%; P = .515). Any grade toxicities (sorafenib vs. placebo) included palmar-plantar erythrodysesthesia syndrome (79.2% vs. 59.6%), diarrhea (47.3% vs. 37.8%), mucosal inflammation (15.4% vs. 6.7%), and hypertension (26.2% vs. 5.6%). Grade 3/4 toxicities included PPES (15.4% vs. 7.1%), diarrhea (4.2% vs. 6.4%), and vomiting (3.5% vs. 0.7%). Conclusion: The combination of sorafenib with capecitabine did not improve PFS, OS, or ORR in patients with HER2-negative advanced breast cancer. Rates of Grade 3 toxicities were higher in the sorafenib arm.